Extending the workspace of parallel working mechanisms - Alp, H.; Özkol, İ. (SAGE Publications, 2008)
The aim of this study is to present a new model to extend the workspace of a parallel working machine in a chosen direction. Therefore, the existing mathematical models are combined and developed to represent the extension of the workspace of a 6° parallel working machine. For this purpose, the 6-3 Stewart platform mechanism (SPM), which is commonly used in robotic applications, material processing, and flight simulation, and the 6-4 SPM have been chosen. Although there are many studies on parallel mechanisms, the workspace analysis of a parallel working mechanism has not yet been generalized. This study determines the workspace of a parallel working mechanism in the direction perpendicular to the moving platform, which is the most workable direction. For these types of working mechanisms, i.e. mechanical tools used for material processing that is forced to move in a certain chosen direction, the determination of the point in that direction at which the workspace is maximum has to be outlined. After carrying out a kinematic analysis, the discretization method, which is based on Euler angles, is used to represent the orientation workspace of these parallel working mechanisms. Additionally, the orientation workspaces of the 6-3 SPM and the 6-4 SPM are compared. Results are presented in a cylindrical coordinate system.